THE CONTRIBUTION OF CIBODAS BOTANIC GARDEN AS AN EX-SITU CONSERVATION SITE FOR TROPICAL MOUNTAINOUS PLANTS: THE LAST DECADE - Imawan Wahyu Hidayat; Neneng Ine Kurnita; Dimas Ardiyanto (Universitas Mataram, 2019)
Abstract: The threats to the plant biodiversity become more advance along with rapid degradation of the natural habitat. Plants preservation needs accompaniment between in-situ and ex-situ conservation altogether. The ex-situ plant conservation plays more important roles in order to help conserve threatened plant species. Cibodas Botanic Garden (CBG) is a government institution which has the main assignment on ex-situ plant conservation, especially tropical mountainous plants. In the last decade, CBG has conducted exploration and plants collection in order to retrieve them from the destructive pressures in their habitat. This study aimed to asses the CBGÃ¢â¬â¢s contribution to ex-situ plant conservation through the addition number of planted plants and to describe the important value to conservation. The study conducted through a quantitative descriptive method, based on data inventory of the newly planted plant in the garden from 2008 to 2018. This also assessed the increasing collection of each year and descriptively explaining the background data, species variety, and their conservation status. The results described that the additional number was 473 specimens and the average increase was 43 specimens per-year. These originated from exploration and plants collection 248 specimens, donation 217 specimens, self-propagation seven specimens, and one specimen from seeds exchange. The most planted was Nepenthaceae with 84 specimens, secondly Phillantaceae with 21 specimens, and Lauraceae 15 specimens. There were 116 species (152 specimens) which have conservation status. These expected to be a comprehensive description of the CBGÃ¢â¬â¢s plant collection and meaningful for the conservation efforts in general.Keywords: ex-situ plant conservation; garden collection; Cibodas Botanic Garden (CBG)